Determinants of Customer Satisfaction That Impact Electricity Repurchase Decisions: Evidence From Electricity Companies in Indonesia - Mohammad Ahsan; Aminullah Assagaf; Slamet Riyadi; Sukesi Sukesi; Eddy Yunus; Sri Utami Ady; Suyanto Suyanto (Dinasti International Journal of Education Management And Social Science, 2023)
The purpose of this study is to determine the effect of marketing mix and service quality on customer satisfaction and its impact on electricity repurchase decisions, a case study on electricity companies in Indonesia. This research uses power electricity product categories and customer service provided by electricity companies. The population of this study is electricity customers spread throughout the territory of Indonesia using questionnaires of 250 respondents. This study used a multiplier regression analysis technique with SPSS Statistical Version 25 statistical processing. Research results, First, electricity customer satisfaction is significantly influenced by price, distribution channels, promotions, and service quality;  Second, customer satisfaction has a positive and significant effect on the decision to repurchase electricity, Third, simultaneously product, price, distribution channel, promotion, and service quality have a significant effect on customer satisfaction and repurchase decisions, Fourth, customer satisfaction can mediate the influence of price, distribution channels, promotions, and service quality on repurchase decisions,   But it is unable to mediate the influence of the product. The results of this study enrich the empirical literature on Marketing Mix theory, Service Quality, Customer Satisfaction, and Purchasing Decisions. Electricity companies can implement a marketing mix and service quality to improve customer satisfaction and electricity repurchase decisions. The originality of this study on mediating customer satisfaction on the effect of marketing mix and service quality on electricity repurchase decisions, no previous study has examined its effect on electricity companies in Indonesia.